Análisis de los ingresos del almacén Marún del cantón Babahoyo - León Olvera, Ilenia Vanessa (2019)
The Warehouse Marún of the Babahoyo Canton, is a commercial company which is dedicated to the wholesale and minor sale of textile products, which came to increase to 6 stores, and currently it is maintained with only one store located in the city of Babahoyo. The present case study work deals with the analysis of the income which was carried out in the Marún Warehouse where the income generated in the same was examined, for the good functioning of the company. Revenue is of utmost importance in a company, since it depends on them that it exists and can work properly, in order to satisfy all the needs of the company. In addition, the income in a company implies an increase in its assets or in turn a decrease in its liabilities. There are several factors that determine their ups and downs such as the price of sale to the public, stock of merchandise, holidays, customer service, among others; that is why you must take care of these aspects that are what define the existence of the company. The case is oriented in the career research sub-line of Accounting Information Management due to the analysis of the revenues of the Marún Warehouse. As support for the research, the knowledge obtained through observations and conversations with those that make up the Marún Warehouse can be enhanced, as well as the use of reliable information sources such as bibliographic data, books, Financial Statements, sales records, invoices, etc. , in order to understand the reasons why there is no adequate control of their income.